2018
DOI: 10.1364/ol.43.000259
|View full text |Cite
|
Sign up to set email alerts
|

Optically induced transparency in bosonic cascade lasers

Abstract: Bosonic cascade lasers are terahertz (THz) lasers based on stimulated radiative transitions between bosonic condensates of excitons or exciton-polaritons confined in a trap. We study the interaction of an incoming THz pulse resonant in frequency with the transitions between neighboring energy levels of the cascade. We show that at certain optical pump conditions the cascade becomes transparent to the incident pulse: it neither absorbs nor amplifies it, in the mean field approximation. The populations of interm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…3 Furthermore, electromagnetically induced transparency in the THz range of such bosonic cascades was also demonstrated. 4 More 'traditional' sources of THz radiation include Gunn devices and tunnel diodes, 5 quantum cascade lasers, 6,7 free-electron based sources, 8 as well as laser-driven emitters of Cherenkov radiation in the THz range. 9 Recently, it has been shown that systems containing exciton polaritons can provide an efficient tunable source of THz radiation, 10,11 and a THz laser using dipolaritons has been proposed.…”
mentioning
confidence: 99%
“…3 Furthermore, electromagnetically induced transparency in the THz range of such bosonic cascades was also demonstrated. 4 More 'traditional' sources of THz radiation include Gunn devices and tunnel diodes, 5 quantum cascade lasers, 6,7 free-electron based sources, 8 as well as laser-driven emitters of Cherenkov radiation in the THz range. 9 Recently, it has been shown that systems containing exciton polaritons can provide an efficient tunable source of THz radiation, 10,11 and a THz laser using dipolaritons has been proposed.…”
mentioning
confidence: 99%
“…The authors proposed a new scheme where excitons are used instead of electrons, exploiting the equidistant levels of a PQW to form the ladder. The bosonic cascade is defined as a series of bosonic energy levels with equal, in the THz range, energy spacing [52]. A boson excited in the highest level can follow a chain of transitions, generating multiple THz photons.…”
Section: Terahertz Radiation and Bosonic Cascadementioning
confidence: 99%
“…The difference between a bosonic cascade and a fermionic one, is that in the bosonic system, the strength of relaxation processes is enhanced by bosonic stimulation. The bosonic final state stimulation enhances the scattering rates such that even in the limit of a weak spontaneous scattering rate, particles can reach the ground level of the cascade [52].…”
Section: Terahertz Radiation and Bosonic Cascadementioning
confidence: 99%
See 2 more Smart Citations